Pharmaceutical nanocrystals: production by wet milling and applications. Issue 3 (March 2018) - Malamatari, Maria; Taylor, Kevin M.G.; Malamataris, Stavros; Douroumis, Dennis; Kachrimanis, Kyriakos
Highlights: Nanocrystals are nanosized drug particles produced in the form of nanosuspensions. Nanocrystals are an industrially feasible formulation for poorly soluble drugs. Wet milling is a scalable and universal production method for nanocrystals. Nanocrystalline systems have been developed for various routes of administration. Abstract : Nanocrystals are regarded as an important nanoformulation approach exhibiting advantages of increased dissolution and saturation solubility with chemical stability and low toxicity. Nanocrystals are produced in the form of nanosuspensions using top-down (e.g., wet milling or high pressure homogenization) and bottom-up methods (e.g., antisolvent precipitation). Wet milling is a scalable method applicable to drugs with different physicochemical and mechanical properties. Nanocrystalline-based formulations, either as liquid nanosuspensions or after downstream processing to solid dosage forms, have been developed as drug delivery systems for various routes of administration (i.e., oral, parenteral, pulmonary, ocular, and dermal). In this review, we summarize and discuss the features, preparation methods, and therapeutic applications of pharmaceutical nanocrystals, highlighting their universality as a formulation approach for poorly soluble drugs. Teaser: This review outlines the advantages, stabilization, and production of drug nanocrystals with an emphasis on wet milling. Covering their pharmaceutical applications, it reveals why nanocrystals are an industrially feasible formulation strategy.